2022
DOI: 10.1093/nar/gkac959
|View full text |Cite
|
Sign up to set email alerts
|

TISCH2: expanded datasets and new tools for single-cell transcriptome analyses of the tumor microenvironment

Abstract: The Tumor Immune Single Cell Hub 2 (TISCH2) is a resource of single-cell RNA-seq (scRNA-seq) data from human and mouse tumors, which enables comprehensive characterization of gene expression in the tumor microenvironment (TME) across multiple cancer types. As an increasing number of datasets are generated in the public domain, in this update, TISCH2 has included 190 tumor scRNA-seq datasets covering 6 million cells in 50 cancer types, with 110 newly collected datasets and almost tripling the number of cells co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(125 citation statements)
references
References 35 publications
2
123
0
Order By: Relevance
“…Tumor Immune Single-cell Hub 2 (TISCH2) is an scRNA-seq database, which aims to characterize TMEs at single-cell resolution. TISCH2 ( http://tisch.comp-genomics.org ) has collected 187 sets of high-quality tumor single-cell transcriptome data and corresponding patient information from GEO and ArrayExpress ( 31 ). The data cover 50 cancer types, including 6 million cells from more than 1,500 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor Immune Single-cell Hub 2 (TISCH2) is an scRNA-seq database, which aims to characterize TMEs at single-cell resolution. TISCH2 ( http://tisch.comp-genomics.org ) has collected 187 sets of high-quality tumor single-cell transcriptome data and corresponding patient information from GEO and ArrayExpress ( 31 ). The data cover 50 cancer types, including 6 million cells from more than 1,500 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Correlation analysis was applied to clarify the SDHs expression in connection with the expressions of immune-related genes. The Tumor Immune Single-Cell Hub (TISCH) database ( http://tisch.comp-genomics.org/home/ ), a scRNA-seq database focusing on the tumor microenvironment, was employed to analyze the correlations between SDHs expression and infiltrating immune cells ( 35 ). Gene expression data was gained from the GEO database (GSE146771), including 10468 single cells from 10 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the CRRS was significantly inversely related to tumor mutation burden (TMB) (Figure 5B), and the combination of CRRS and TMB could better predict the overall survival of UCEC patients (Figure 5C). Microsatellite instability hypermutated (MSI-H) tumors account for approximately 25% to 30% of endometrial carcinomas (42), which have DNA mismatch repair defects, resulting in errors in repetitive DNA sequences known as microsatellites (41,43). As shown in Figure 5D, the MSI-H subtype had a lower CRRS.…”
Section: Comprehensive Genomic Alterations Analyses In Different Crrs...mentioning
confidence: 99%
“…We further verified the relationship between APOBEC3G and CD8A/ GZMB by qRT-PCR, and the results demonstrated that the two variables were positively correlated (Figure S8D). Then, we investigated the heterogeneity expression pattern of APOBEC3G, CD8A, and GZMB in different immune cells at a single-cell level using TISCH2 (UCEC-GSE139555) (43), and found that they were mainly expressed in CD8 + T cells (Figure S8E). Next, we explored associations between CRRS and signatures of antitumor immunity.…”
mentioning
confidence: 99%